The parliamentary dimension of regional integration. A comparison of the European Union and MERCOSUR - Vazquez, Mariana (2006)
This article analyzes the development of parliamentary institutions in processes of regional integration. Its focus is on two cases, the European Union and MERCOSUR, and their respective parliamentary bodies: the European Parliament and the Joint Parliamentary Commission of MERCOSUR. The article looks into whether and how ongoing processes of regional integration are transforming the historical role performed by parliamentary bodies, and evaluates the degree to which path-dependency impinges on such transformations